Pengaruh Pendapatan Sektor Pariwisata Dan Budaya Terhadap Pendapatan Asli Daerah Kabupaten Kutai Kartanegara - Hermanto, Muhammad (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2008)
The income of tourism and culture sector of Kutai Kartanegara Regency, is the results which be gotten from Department of culture and tourism of Kutai Kartanegara Regency include hotel tax, restaurant tax and object and tourism location ticket retribution that exist in Kutai Kartanegara. The income of tourism and culture sector of Kutai Kartanegara Regency is one of element from original income in Kutai Kartanegara. Meanwhile the original income of Kutai Kartanegara is gotten from income which dig from the certain sources in some places include territory tax, territory retribution, surplus from local company and wealth  management result  from other territory is separated and the other legitimated income.  According to the experiment in the field. The result from the income and culture sector of Kutai Kartanegara as 3 years get decrease: Year 2001 as amount Rp. 2.794.084.935,45Year 2002 as amount Rp. 2.306.826.205,58Year 2003 as amount Rp. 2.101.356.647,56This case shows that the human source of tourism and culture in Kutai Kartanegara Regency still poor. So that the manager of tourism asset who is the profit center for the government of Kutai Kartanegara Regency haven’t optimal enough.  Key Word : Income, Tourism secto